Comparison of antihypertensive drug utilization in community health centre and type B teaching hospital - Sitorus , Tromphin; Simatupang, Abraham (Talenta Publisher, 2023)
Antihypertensive medicine is one of the many complex factors contributing to the sustained rise in hypertension prevalence, which remains a global health concern. The Social Security Agency on Health, or Badan Penyelenggara Jaminan Social (BPJS) Kesehatan, in Indonesia is an integrated healthcare system that provides universal healthcare to its citizens. This retrospective cross-sectional study examined the use of antihypertensive medications covered by BPJS between January and December 2021 at the Rawabuntu Primary Health Centre and the Universitas Kristen Indonesia (UKI) type B public hospital. The necessary data was extracted from the medical files of 192 hypertensive patients. The patients' characteristics were analysed descriptively. The rationality of antihypertensive medication use was evaluated in accordance with Association of Indonesian Hypertension Physicians-approved guidelines. The majority of patients in both categories were female (52.1 percent at the Rawabuntu Primary Health Centre and 60 percent at the teaching facility). In both healthcare facilities, the correct indication, patient, and dosage were administered 100 percent of the time, according to this study. While only 66.7% and 85.4% of patients at the Rawabuntu Primary Health Centre and UKI hospital received the correct drug category, respectively. The rational use of antihypertensive medications was substantially lower at the Primary Health Centre than it was at the UKI Hospital (p = 0.001).